Dynamics of Viral Abundance and Diversity in a Sphagnum-Dominated Peatland: Temporal Fluctuations Prevail Over Habitat - Ballaud, Flore; Dufresne, Alexis; Francez, André-Jean; Colombet, Jonathan; Sime-Ngando, Télesphore; Quaiser, Achim (Frontiers in Microbiology, 2016)
Viruses impact microbial activity and carbon cycling in various environments, but their diversity and ecological importance in Sphagnum-peatlands are unknown. Abundances of viral particles and prokaryotes were monitored bi-monthly at a fen and a bog at two different depths. Viral particle abundance ranged from 1.7x106 to 5.6x108 particles mL-1, and did not differ between fen and bog but showed seasonal fluctuations. These fluctuations were positively correlated with prokaryote abundance and dissolved organic carbon, and negatively correlated with water-table height and dissolved oxygen. Using shotgun metagenomics we observed a shift in viral diversity between winter/spring and summer/autumn, indicating a seasonal succession of viral communities, mainly driven by weather-related environmental changes. Based on the seasonal asynchrony between viral and microbial diversity, we hypothesize a seasonal shift in the active microbial communities associated with a shift from lysogenic to lytic lifestyles. Our results suggest that temporal variations of environmental conditions rather than current habitat differences control the dynamics of virus-host interactions in Sphagnum-dominated peatlands.